Peanut leaf transcriptomic dynamics reveals insights into the acclimation response to elevated carbon dioxide under semiarid conditions - Laza, Haydee; Bhattarai, Bishwoyog; Mendu, Venugopal; Burow, Mark D.; Emendack, Yves; Sanchez, Jacobo; Gupta, Aarti; Abdelrahman, Mostafa; Tran, Lam-Son Phan; Tissue, David T.; Payton, Paxton (Frontiers in Plant Science, 2025)
Introduction Elevated atmospheric carbon dioxide [CO2] increases peanut carbon assimilation and productivity. However, the molecular basis of such responses is not well understood. We tested the hypothesis that maintaining high photosynthesis under long-term elevated [CO2] is associated with the shift in C metabolism gene expression regulation. Methods We used a field CO2 enrichment system to examine the effects of elevated [CO2] (ambient + 250 ppm) across different soil water availability and plant developmental stages on the molecular responses in a peanut runner-type genotype. Plants under both [CO2] treatments were grown in semiarid conditions. We evaluated a comparative leaf transcriptomic profile across three periodic water deficit/re-hydration (well-watered/recovery) cycles throughout the growing season using RNAseq analysis. Results Our results showed that the transcriptome responses were influenced by [CO2], water availability, and developmental stages. The traditional Mercator annotation analysis based on percentage total revealed that lipid metabolism, hormone biosynthesis, secondary metabolism, amino acid biosynthesis, and transport were the most regulated biological processes. However, our new approach based on the comparative relative percentage change per individual category across stages revealed new insights into the gene expression patterns of biological functional groups, highlighting the relevance of the C-related pathways regulated by elevated [CO2]. Discussion The photosynthesis analysis showed that 1) The light reaction was the most upregulated pathway by elevated [CO2] during water stress, 2) Photorespiration was downregulated across all stages, 3) Sucrose synthesis genes were upregulated by elevated [CO2] before stress, 4) Starch synthesis genes were upregulated by elevated [CO2] under drought periods, and 5) CO2 regulation of sucrose and starch degradation was critical under drought periods. Our findings provide valuable insights into the molecular basis underlying the photosynthetic acclimation response to elevated [CO2] in peanuts.